On the circumference of circle Γ , chord A B with length 1 1 0 0 is drawn. Let C be the midpoint of A B . Through C , 2 other chords D E and F G are also drawn, such that the points around the circle are A , D , F , B , E , G . The line segment A B intersects D G and F E (internally) at H and I , respectively.
If A H = 4 4 9 , what is C I ?
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
By the Butterfly theorem, we see that C is the midpoint of HI.
Since C is the midpoint of HI, C I = C H .
Since C is the midpoint of AB, C A = C B = 2 A B
Thus, C I = C H = C A − A H = 2 A B − A H = 2 1 1 0 0 − 4 4 9 = 1 0 1
Butterfly theorem states that C I = C H , hence C I = C H = A C − A H = 5 5 0 − 4 4 9 = 1 0 1 .
To prove butterfly theorem, observe that F I = C I sin ∠ E F G sin ∠ F C A and I E = C I sin ∠ F E D sin ∠ E C A . From power of a point, we have
C I 2 sin ∠ E F G sin ∠ F E D sin ∠ F C A ⋅ sin ∠ E C A = F I ⋅ I E = I A ⋅ I B = ( A C + C I ) ( B C − C I ) = C A 2 − C I 2 Hence C A 2 = C I 2 ( 1 + sin ∠ E F G sin ∠ F E D sin ∠ F C A ⋅ sin ∠ E C A ) . Similarly for H, we have C B 2 = C H 2 ( 1 + sin ∠ E D G sin ∠ F G D sin ∠ D C B sin ∠ B C G ) .
Since ∠ F C A = ∠ B C G , ∠ E C A = ∠ D C B , ∠ E F G = ∠ E D G and ∠ F E D = ∠ F G D , the coefficients are the same, so C H = C I .
we draw an imaginary circle.according to given condition we draw required segment.as given that c is mid point& we know that aline drawn from centre perpendicular to chord divides i.e. cis the mid point.
Problem Loading...
Note Loading...
Set Loading...
The butterfly theorem states that if C is the center of a chord A B in a circle, chords D E and F G pass through C and A B intersects D G and F E at H and I respectively, then C is the midpoint of I H . In this case we now know that C I = C H = A C − A H = 5 5 0 − 4 4 9 = 1 0 1 , as desired.